The Effect of Green Marketing, Brand Awareness and Price Perception on Purchase Decision - Alviccenia Lailatul Mukaromah; I Gusti Ngurah Agung Eka Teja Kusuma; Ni Putu Nita Anggraini (International Journal of Applied Business and International Management, 2019)
Customers in choosing products will choose based on what is most needed and what is most suitable for them. Purchasing decisions can be influenced by various factors including green marketing, brand awareness and price perception. The purposes of this study are analyzing the effect green marketing, brand awareness, price perceptions on purchase decisions. The sample used in this study as many as 90 respondents were determined by purposive sampling. The data analyzed using multiple linear regression The results of this study are green marketing, brand awareness, price perceptions have a positive effect on purchase decisions